2018
DOI: 10.1155/2018/1826170
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Properties of Graviola (Annona muricata): A Comprehensive Mechanistic Review

Abstract: Graviola (Annona muricata) is a small deciduous tropical evergreen fruit tree, belonging to the Annonaceae family, and is widely grown and distributed in tropical and subtropical regions around the world. The aerial parts of graviola have several functions: the fruits have been widely used as food confectionaries, while several preparations, especially decoctions of the bark, fruits, leaves, pericarp, seeds, and roots, have been extensively used in traditional medicine to treat multiple ailments including canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
120
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 134 publications
(263 reference statements)
5
120
0
10
Order By: Relevance
“…Our results are consistent with earlier reviews, in respect to identifying consistent reports of the antiulcerative, anti‐inflammatory, antinociceptive and chemopreventive effects of A. muricata leaf extract. This review focused on summarising clinically relevant data to add to the body of knowledge about the safety and tolerability of A. muricata leaf extract.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results are consistent with earlier reviews, in respect to identifying consistent reports of the antiulcerative, anti‐inflammatory, antinociceptive and chemopreventive effects of A. muricata leaf extract. This review focused on summarising clinically relevant data to add to the body of knowledge about the safety and tolerability of A. muricata leaf extract.…”
Section: Discussionmentioning
confidence: 99%
“…Although all aerial parts of A. muricata are used in traditional medicine practices, the leaf is the most widely used in current commercially available products. The acetogenins have been identified as one of the main bioactive constituents of A. muricata . Previous reviews have reported some safety and tolerability data specifically focused on preclinical studies .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported in the literature that nearly 74 bioactive compounds of the plant exhibit a variety of anticancer effects in in vitro and in vivo animal model systems. A. muricata-derived preparations and formulations have been used for the treatment of different disease conditions, thereby proving its prominence in Ethnomedicine [18]. The bark, leaves, and roots of Annona muricata have been extensively applied globally in the disease management of various ailments, including inflammatory conditions, rheumatism, diabetes, hypertension, insomnia, cystitis, parasitic infections, and cancer [19].…”
Section: Anticancer Effects Of Annona Muricata's Fruit-graviolamentioning
confidence: 99%